2014
DOI: 10.7314/apjcp.2014.15.18.7575
|View full text |Cite
|
Sign up to set email alerts
|

Five miRNAs as Novel Diagnostic Biomarker Candidates for Primary Nasopharyngeal Carcinoma

Abstract: MicroRNAs (miRNAs) play an essential role in the development and progression of nasopharyngeal carcinomas (NPC). Despite advances in the field of cancer molecular biology and biomarker discovery, the development of clinically validated biomarkers for primary NPC has remained elusive. In this study, we investigated the expression and clinical significance of miRNAs as novel primary NPC diagnostic biomarkers. We used an array containing 2, 500 miRNAs to identify 22 significant miRNAs, and these candidate miRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Family members of the miR-183 are proposed as promising biomarkers for early cancer detection, prognosis, and as therapeutic targets in several cancers [ 65 - 67 ]. However, the results of their expression profiling in cancer tissues are inconsistent and controversial (Reviewed in [ 68 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Family members of the miR-183 are proposed as promising biomarkers for early cancer detection, prognosis, and as therapeutic targets in several cancers [ 65 - 67 ]. However, the results of their expression profiling in cancer tissues are inconsistent and controversial (Reviewed in [ 68 ]).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs constitute a family of small non-coding RNAs that are approximately 22 nucleotides in length [5], and these molecules can play oncogenic or tumor suppressor roles during tumorigenesis by influencing malignant biological behaviors such as proliferation, apoptosis, radioresistance, chemoresistance, and metastasis [6][7][8][9]. miR-93-5p, an miRNA within the miR-106b- 25 cluster, has been reported to be dysregulated in various types of cancer such as cervical, breast, and bladder cancers, as well as nasopharyngeal carcinoma [10][11][12][13]. Our previous study demonstrated that miR-93-5p is upregulated in SCCHN tissues, and this upregulation is closely related to the clinicopathological parameters of T status, lymph node metastasis, and clinical stage [14].…”
Section: Ivyspringmentioning
confidence: 99%
“…Two of the upregulated NW miRNAs, hsa-miR-93 and hsa-miR-205 concurred with the findings of other studies. 19,20 Both hsa-miR-93 and hsa-miR-205 were shown to be upregulated in NPC tissue samples 21,22 and could lead to enhance cell growth, migration and invasion in NPC cell lines. 21,23 Meanwhile, hsa-miR-21 and hsa-miR-421 that were shown to be upregulated in NW were consistent with the trend reported by 1 to 2 NPC tissue profiling studies (Supporting Information Table S1).…”
Section: Nw Ebv Dna Load As Biomarker For Npc Detection and Monitoringmentioning
confidence: 99%